The mission of God's people : a biblical theology of the church's mission - Wright, Christopher J. H. (Grand Rapids, Mich. Zondervan, 2010)
Author Chris Wright offers a sweeping biblical survey of the holistic mission of the church, providing practical insight for today's church leaders. Wright gives special emphasis to theological trajectories of the Old Testament that not only illuminate God's mission but also suggest priorities for Christians engaged in God's world-changing work.
Keywords: Mission of the church. Missions. Church work